Satisfaction segmentation among finance company customers - Speece, Mark (2011)
This paper reports on a survey of customer satisfaction with a credit company’s services inKhorasan Jonobi, Iran. We followed Mihelis et al . [1] in using their five dimensions and their measures. Someresearchers have begun to call for segmentation analysis based on satisfaction and we have done that here.There are four distinct segments. One has high satisfaction across all dimensions, one was relatively low onall of them. Two segments were midway on most dimensions, but one was positive about the personnel, onenegative. These results show that the managerial problem here is not entirely about upgrading serviceoperations. Rather, it is a targeting and positioning problem for marketing